Steps Toward the Band Gap Identification in Polystyrene Based Solid Polymer Nanocomposites Integrated with Tin Titanate Nanoparticles - M. Hussein, Ahang (Polymers (Basel), 2020)
In the current study, the film fabrication of polystyrene (PS) based polymer nanocomposites (NCs) with tuned refractive index and absorption edge was carried out using the solution cast method. X-ray diffraction (XRD) and ultraviolet-visible (UV-Vis) light characterization techniques were performed. The structural and optical properties of the prepared films were specified. The hump of PS decreased significantly when SnTiO(3) nanoparticles (NPs) were introduced. Sharp and high intense peaks of SnTiO(3) NPs at a high filler ratio were observed. The crystalline size was determined for SnTiO(3) NPs from the sharp crystalline peaks using Debye-Scherrer’s equation and was found to be 25.179 nm, which is close enough to that described by the supplier. Several optical parameters, such as absorption coefficient (α), refractive index (n), and optical dielectric properties, were investigated. The absorption spectra were tuned with increasing SnTiO(3)NPs. Upon the addition of the NPs to the PS host polymer, the absorption edge undergoes shifting to lesser photon energy sides. The optical dielectric constant (ε′) was correlated to the refractive index. The study of the optical band gap was conducted in detail using both Tauc’s model and the optical dielectric loss (ε″) parameter. The results showed that the ε″ parameter is noteworthy to be measured in the optical band gap study of materials.